Circulating PCSK9 levels and 2-hPG are positively correlated in metabolic diseases in a Chinese Han population - Wen Guo; Yingyun Gong; Yong Gu; Zhenzhen Fu; Hongqi Fan; Beibei Gao; Xiaohui Zhu; Jinxiang Fu; Yang Zhao; Min Sun; Xing Liu; Xian-Cheng Jiang; et al. (Lipids in Health and Disease, 2018)
Abstract Background Proprotein convertase subtilisin/kexin type 9 (PCSK9), which plays a crucial role in lipoprotein metabolism, has been also regarded as an important marker for atherosclerosis. Available evidence indicated that 2-h postchallenge plasma glucose (2-hPG) could be another biomarker for atherosclerosis. However, currently the association between circulating PCSK9 and 2-hPG remains unclear. Here, we explored this potential link in a Chinese Han population. Methods Totally, 600 Chinese Han subjects from Nanjing district, China, were enrolled for the 75-g oral glucose tolerance test (OGTT), and they included normal glucose tolerance (NGT, n = 200), impaired glucose regulation (IGR, n = 200), and type 2 diabetes (T2DM, n = 200). Anthropometric and biochemical determinations such as serum lipid measurements were made. A sandwich ELISA assay was performed to measure serum PCSK9 levels in all subjects. Results Serum PCSK9 concentrations were higher in IGR group (77.63 ± 28.14 ng/ml) and T2DM group (90.62 ± 39.96 ng/ml) than in NGT group (65.33 ± 32.68 ng/ml), and it was significantly higher in T2DM group than in IGR group (p < 0.01). Serum PCSK9 levels positively correlated with 2-hPG and LDL-C in all subgroups, but presented a positive correlation with fasting blood glucose (FBG) only in T2DM group. Using multiple regression model analysis, we also found that PCSK9 levels closely correlated with 2-hPG in all tested groups. According to multinomial logistic regression analysis, PCSK9 levels positively correlated with T2DM (OR = 1.017[1.010–1.025], p < 0.001) even after adjustment for lipid levels. Moreover, in subjects with normal FBG level, 2-hPG gradually and significantly increased across PCSK9 tertiles (6.68 ± 2.01, 7.48 ± 2.10 and 8.27 ± 2.41 mmol/L, respectively, p < 0.01); however, in subjects with normal 2-hPG levels, no such difference was observed. Conclusions PCSK9 levels increase as glucose metabolism deteriorated. Serum PCSK9 levels positively correlated with 2-hPG in patients with metabolic diseases.